Effectiveness of Government Intervention in Regulating Tax and Incentives Towards Indonesia’s Blue Economy Sustainability - Nur Rachma Fitriani; Rahayu, Alita Indah; Paramartha, Herlina Rifa (Journal of World Trade Studies, 2024)
Indonesia is now focusing on developing more inclusive and sustainable economic growth in the maritime sector. The potential of Indonesia’s marine resources has become the focus of transformation in terms of implementing the blue economy framework. The tourism and maritime sectors are among the largest contributors to the Indonesian economy. However, the analysis and application of the blue economy to the socio-economy of coastal communities have still not received much attention. Previous research on this topic is still limited, particularly regarding the impact of related policies and regulations. Therefore, this paper aims to evaluate the effectiveness of government intervention in imposed tax and incentive provisions as leading factors for implementing a sustainable blue economy. This paper also aims to analyze further the potential and challenges in developing Indonesia’s marine economy. This paper will use the methodology of secondary data analysis and case studies with the approach of public economics. The findings of this paper are recommendations for policy reform to support the blue economy transition in Indonesia, such as mobilizing incentives, developing better resource management systems, and strengthening institutional capacity.